Role modeling in physical education - Colin Pennington (spdfharmony.com, 2025)
Background: The role of Physical Education (PE) teachers as role models plays a crucial part in shaping students’ healthy lifestyles and positive character development. Various curriculum models such as the sport education model, personal and social responsibility model, and health-related fitness (HRF) model offer different approaches to achieving learning goals, but they do not fully address the holistic role of teachers as role models. Aims: This study aims to explore PE teachers’ perceptions of their role as holistic role models in fostering students’ physical, social, emotional, and moral development. Methods: This research employs a descriptive qualitative approach guided by the Standards for Reporting Qualitative Research (SRQR). Eight PE teachers from elementary and secondary schools were purposively selected. Data were collected through semi-structured interviews, transcribed verbatim, and analyzed using inductive thematic analysis. Data validity was ensured through triangulation and member checking. Results: The findings indicate that teachers view role modeling as encompassing not only physical demonstration but also the embodiment of moral values, social responsibility, and emotional regulation. The HRF model was criticized for focusing too heavily on physical fitness, thus limiting opportunities for teaching social and moral values. Students’ perceptions of teachers as role models were also influenced by physical appearance factors such as age and body weight. Conclusion: These findings highlight the importance of a holistic approach in physical education and the need for teacher training that integrates physical, emotional, and value-based competencies. Through thoughtful role modeling, PE can become a meaningful avenue for character development and the promotion of lifelong healthy behaviors.